Harrison Birtwistle : Man, mind, music - Cross, Jonathan 1961- (s.l. Cornell University Press, 2000)
Sir Harrison Birtwistle is the most original, the most challenging, and the most controversial British composer of our time. His notoriously angular music is at once defiantly modernist and deeply indebted to the traditions, medieval and modern, of English music.Birtwistle composes for ensembles of every size and shape but is perhaps best known for his music for the opera stage. His opera Gawain, possibly his most famous work, is fully characteristic in its marriage of a modernist musical language and a mythic subject.Accessible to anyone with an interest in modern music, this book uncovers the sources of Birtwistle's art and presents a critical account of his musical, dramatic, and aesthetic preoccupations through an exploration of such topics as theater, myth, ritual, pastoral, pulse, and line. It places Birtwistle in a broad cultural context, examining the composers and painters who have influenced his work.